Automated Power Source Selection System for Uninterrupted Supply: Integration of Main Power, Solar Energy, and Generator Power - Ukagwu, Kelechi John; Kapalata, Prosper; Eze, Val Hyginus Udoka (Journal of Engineering, Technology, and Applied Science (JETAS), 2024)
A consistent power supply is indispensable across various sectors, spanning from households to critical institutions like research facilities, hospitals, and financial institutions. This study endeavors to ensure uninterrupted power provision to a load through an automated selection process among three primary power sources: main power, solar energy, and generator power, with main power being the primary preference. Implemented using an 8051 microcontroller, the system is linked to three switches representing each power source for simulation purposes. Upon detection of a switch release or deactivation, signifying the absence of that particular power source, the microcontroller promptly deactivates the corresponding relay driver. This relay driver then switches the relevant relay, facilitating seamless power continuity to the load if any switch is activated. A lamp or bulb serves as a demonstrative load powered by the primary source. In the event of a power outage, the system seamlessly transitions to the next available source, such as solar energy, and if required, to generator power. An LCD is employed to indicate the currently active power source, ensuring operational transparency and facilitating swift troubleshooting when necessary.